11 Eylül 2001 sonrası Türkiye’de din merkezli batı stratejileri - Öztürk, Mustafa Tahir (My University, 2010)
nlerarası Diyalog, Strateji, Teo-strateji, Misyonerlik, 11 Eylül Olayı ÖZET 11 EYLÜL 2001 SONRASI TÜRKİYE’DE DİN MERKEZLİ BATI STRATEJİLERİ II. Dünya Savaşı’ndan sonra başlayan süreçte, başını ABD’nin çektiği Batı Dünyası, stratejilerinin merkezine dini oturtmuştur. Bu sürecin üç önemli aşaması olmuştur. Birincisi, 1965 yılında başlayan dinlerarası diyalog aşaması; ikincisi SSCB’nin dağılması, üçüncü ve en dikkat çekici aşaması 11 Eylül Olayı’dır. Anılan süreçte İslam, Hıristiyanlık karşısında en büyük rakip ve dolayısıyla en büyük tehlike; Türkiye ise din merkezli bu stratejilerin muhatabı olan en önemli ülkesi olmuştur. “11 Eylül 2001 Sonrası Türkiye’de Din Merkezli Batı Stratejileri” adlı çalışmamızda temelde 11 Eylül Olayı sonrası Hıristiyan Batı Dünyası’nın teo-stratejilerinin ana hedef ülkesi durumunda olan Türkiye’deki yansımaları ele alınmıştır. Araştırmamız giriş, dört bölüm, sonuç, ekler ve bibliyografyadan oluşmaktadır. Girişte araştırmanın konusu, amacı, önemi, iddia ve varsayımları, sınırları, yöntemi, ilgili literatür, temel kavramlar, teorik çerçeve ve plan ele alınmaktadır. Birinci bölümde Batı’nın İslam Dünyası ve Türkiye ile ilişkilerinin tarihi arka planı ele alınmıştır. İkinci bölümde Batı’nın din ve siyaset ilişkilerine bakışının temel belirleyicisi olan Pavlus ile İslam ve Türkiye siyasetinin temsili teorisyenleri olan Toynbee ve Huntington ele alınmıştır. Üçüncü bölümde 11 Eylül Olayı tasvir edilmiş ve stratejik sonuçlarına değinilmiştir. Dördüncü bölümde ise Batının Türkiye üzerindeki teostratejik hedeflerinin başlıca göstergelerine değinilmiştir. Name and Surname : Mustafa Tahir Öztürk Field : Theology Programme : Sociology of Religion Supervisor : Associated Professor Ali Coşkun Degree Awarded and Date : Doctorate-July 2010 Interreligious Dialogue, Strategy, Teo-strategy, Missionary, September 11 Event

RELIGION CENTERED WESTERN STRATEGIES IN TURKEY AFTER SEPTEMBER 11, 2001 Western world, under the lead of the United States, has taken “religion” as a core for their international strategies, particularly after the Second World War. This period can be investigated under three different stages. First stage called as the interreligious dialogue stage started in the year of 1965, dissolution of the Soviet Union opened the second stage in 1991. The third and the most striking stage started with the September 11. In the period which embraced three of aforementioned stages, Islam is considered as the most powerful opponent of Christianity and also the biggest danger for it. Hence, Turkey became the most important country which confronted with this religion centered western strategies. This work, entitled “Religion Centered Western Strategies in Turkey after September 11, 2001” focuses mainly on the impact of teo-strategies of Christian Western World on Turkey which became his main target after the September 11. Our research consists of an introduction part, four chapters, the conclusion, appendices and the bibliography. In introduction part the aim and scope, hypotheses, limitation and methodology, briefly theoretical background, of this work are framed. Whilst the first chapter touches briefly on historical background of relations between Western and Islamic World and Turkey, second chapter focuses on Pavlus who is the main determiner of the Western view on religion and politics, Toynbee and Huntington who are the representatives of Western politics for Islam and Turkey. In the third chapter, the September 11 is described and the strategic results of the event are explored. In the last chapter, i.e. fourth one, the main indicators of teo-strategic goals of Western for Turkey are handled.
Keywords: Din Sosyolojisi